2016
DOI: 10.1039/c6ce00965d
|View full text |Cite
|
Sign up to set email alerts
|

Grain rotation and lattice deformation during perovskite spray coating and annealing probed in situ by GI-WAXS

Abstract: Synchrotron grazing incidence WAXS is used to track CH3NH3PbI3 precursor and perovskite crystallites rotation in situ during solution-deposition and thermal annealing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 24 publications
2
59
0
Order By: Relevance
“…These peaks arise due to larger crystalline grains present with various orientations and reveal further information on the present process: Upon annealing, a shift of individual diffraction peaks in radial direction toward higher q values is observed that correspond to individually decreased lattice distances, as seen in Figure S4, Supporting Information. This finding can be attributed to lattice strain during the perovskite conversion from the precursor …”
Section: Resultsmentioning
confidence: 98%
“…These peaks arise due to larger crystalline grains present with various orientations and reveal further information on the present process: Upon annealing, a shift of individual diffraction peaks in radial direction toward higher q values is observed that correspond to individually decreased lattice distances, as seen in Figure S4, Supporting Information. This finding can be attributed to lattice strain during the perovskite conversion from the precursor …”
Section: Resultsmentioning
confidence: 98%
“…They reason that this is caused by nucleation sites at the grain boundaries, which leads to crystal growth at the expense of surrounding grains, leading to strain which causes rotation and lattice deformation. [50] By contemplating ex-situ SEM data they found further proof of grain fragmentation observed in earlier GISAXS studies. [13] Finally, many fabrication methods employ dimethylsulfoxide and other complex forming additives and solvents.…”
Section: Research Newsmentioning
confidence: 89%
“…As both fields are evolving, the future will most probably see even more sophisticated in-situ GIXS measurements looking into perovskite crystallization and degradation processes, along with the development of more complex analysis tools for treatment of large amounts of data as shown by recent studies. [30,32,50] Other possible applications of GIXS include the investigation of more industry-relevant film fabrication methods like roll-to-roll printing. [65] On the other hand, GIXS offers many experimental possibilities that can be exploited in static or quasi-static measurements, and thus are able to give more in-depth knowledge, e.g., by incident angle scans for depth-profiling of samples or making use of focused X-ray beams for mapping of sample homogeneity over larger scales.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A nylon/metal-printed sample chamber filled with Helium was used to reduce background due to air scattering [33]. The X-ray energy was 10 keV and the beam size 100 µm × 260 µm (vert.…”
Section: Methodsmentioning
confidence: 99%